Concrete Performance Using Rice Husk Ash as Partial Cement Replacement: A Review - Kiew, Chiong Ong; Mohd Fahmi Bin Abdul Rahman (Progress in Engineering Application and Technology, 2021)
A review on the Concrete performance using rice husk ash as partial cement replacement. To review the properties of concrete and rice husk ash. Due to high demand of concrete use in the world, there is excessive emission of carbon dioxide causing environment pollution. Modification of concrete using waste material can help to reduce the environment pollution. Rice husk ash (RHA) are organic agriculture product that can help to reduce the pollution in an eco-friendly way. The properties of the concrete on compressive strength, water absorption and thermal conductivity are reviewed. The research proved that with the help of rice husk ash is able to improve the performance of the concrete. The data of the concrete with 0 %, 10 %, 15 % and 20 % is being compared to achieve the best ratio of rice husk ash replacement. The data shows a positive effect in the properties of the concrete.